2022
DOI: 10.1128/jb.00575-21
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of Alarmone Metabolism in Clostridioides difficile

Abstract: Despite the role of the stringent response in antibiotic survival and recurrent infections, it has been a challenging target for antibacterial therapies because it is so ubiquitous. This is an especially relevant consideration for the treatment of Clostridioides difficile infection (CDI), as exposure to broad-spectrum antibiotics that harm commensal microbes is a major risk factor for CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…The presence of pGpp suggests that X. campestris pv. campestris RSHs may be able to produce pGpp, as recently reported in Clostridiodes difficile ( 19 ), or that it contains Nudix hydrolases that can convert (p)ppGpp to pGpp, similar to NahA in B. subtilis ( 12 ). Importantly, the Δ sah mutant showed elevation of pGpp ( Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The presence of pGpp suggests that X. campestris pv. campestris RSHs may be able to produce pGpp, as recently reported in Clostridiodes difficile ( 19 ), or that it contains Nudix hydrolases that can convert (p)ppGpp to pGpp, similar to NahA in B. subtilis ( 12 ). Importantly, the Δ sah mutant showed elevation of pGpp ( Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Alarmone synthetases and hydrolases belong to the RelA/SpoT homologs (RSHs) superfamily ( 16 ), which is further classified into multidomain “long” RSHs or single-domain homologs known as small alarmone synthetases (SASs), or small alarmone hydrolases (SAHs) ( 10 , 15 ). Long RSHs include the synthetase RelA ( 1 ) and the bifunctional synthetase and hydrolase Rel ( 17 ) and SpoT ( 18 ), which produce (p)ppGpp and in some cases pGpp ( 19 ). Examples of SASs include SasA (RelP), SasB (RelQ), and RelV ( 20 23 ), which produce (p)ppGpp and in some cases pGpp ( 24 ) or (p)ppApp ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrophosphotransfer to mono-, di-, and triphosphate adenosine and guanosine molecules has been documented for decades, but only (p)ppGpp was consistently detected in vivo and conclusively linked to a phenotype, and the small amounts of pGpp detected in some assays were easy to dismiss as artifacts or unimportant ( 41 ). It has recently been confirmed that some synthetase enzymes are capable of utilizing GMP as a substrate to synthesize pGpp directly ( 13 , 33 , 37 , 39 , 40 , 45 to 47 ). In addition, hydrolase enzymes can selectively remove 5′-phosphates from longer guanosine alarmones ( 29 , 33 , 43 , 48 to 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Most synthetase enzymes will utilize either GDP or GTP as the substrate but have a higher affinity for one of the nucleotides ( 13 , 34 to 40 ). As the ratio of GDP to GTP in bacterial cytoplasm is a dynamic parameter that changes quickly in response to nutrient conditions, the relative production of ppGpp and pppGpp could reflect substrate availability when alarmone synthesis is activated ( 26 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation